A system dynamics-based environmental benefit assessment model of construction waste reduction management at the design and construction stages - Ding, Zhikun; Zhu, Menglian; Tam, Vivian W.Y.; Yi, Guizhen; Tran, Cuong N.N. (Journal of cleaner production, 2018)
Construction waste generation and its environmental impact reduction have become an urgent issue to be solved with the acceleration of urbanization process in China. However, limited research has been conducted to cover both the design stage and the construction stage such that the overall construction waste reduction outcome could be comprehensively assessed. Based on interview data and literature review, Vensim software was used to build a two-stage environmental benefit assessment system dynamics (SD) model which covered construction waste reduction management subsystem, waste generation and disposal subsystem, and environmental benefit assessment subsystem. Simulation results highlight that the reduction management can reduce 40.63% of waste generation. In the meantime, the reduction management achieves good environmental benefits including the reduction of greenhouse-gas emissions of 12,623.30 kg, saving waste landfill of 3901.05 m3 and reducing the use of public vacant site for the illegal dumping of 688.42 m3. The simulation results demonstrate that the dynamic model could assess the environmental benefits of construction waste reduction effectively at the design and the construction stage. This research can provide insight to the design and construction professionals for waste reduction measures such as prefabricated components application, reduced design modification at the design stage, on-site sorting and material reuse at the construction stage, and to provide references for governments in assessing the reduction management outcomes of construction projects and the environmental benefits. •A two-stage SD model for environmental benefit assessment of CW reduction management was developed.•The implementation of waste reduction management at the design and construction stage can effectively reduce construction wastes and bring significant environmental benefits.•Applications of any single waste reduction measure are limited while multiple waste reduction measures must be implemented simultaneously to achieve the maximum benefits of waste reduction.•The developed model can help professionals for waste reduction practices and references for governments.